Resonant inelastic x-ray spectroscopy on UO2 as a test case for actinide materials. (11th November 2020) - Lander, G H; Sundermann, M; Springell, R; Walters, A C; Nag, A; Garcia-Fernandez, M; Zhou, K J; van der Laan, G; Caciuffo, R
Abstract: Resonant inelastic x-ray spectroscopy at the uranium N4 absorption edge at 778 eV has been used to reveal the excitations in UO2 up to 1 eV. The earlier (1989) studies by neutron inelastic scattering of the crystal-field states within the 3 H4 multiplet are confirmed. In addition, the first excited state of the 3 F2 multiplet at ∼520 meV has been established, and there is a weak signal corresponding to the next excited state at ∼920 meV. This represents a successful application of soft x-ray spectroscopy to an actinide sample, and resolves an open question in UO2 that has been discussed for 50 years. The technique is described and important caveats are drawn about possible future applications.